Characteristics and Emerging Trends in International City Negotiations - M. I. Kolykhalov (Vestnik MGIMO-Universiteta, 2024)
The article examines key features, main directions, and current trends in international negotiations between subnational territorial units using the example of cities. In today’s world, where the global political system is undergoing epochal change, the international activities of non-governmental and subnational actors, including their participation in international negotiations, have intensified. One of the key features of international city negotiations is that they occur mainly in a multilevel and multilateral format. This is due to the hybrid nature of cities, which are both state and non-state entities. The balance of power between cities and states in international relations depends on factors such as the degree of autonomy granted to sub-national units by the central government, as well as the level of economic and political influence held by cities. Sometimes, the position of a city may differ significantly from that of the state it belongs to. At the international level, there are several specialized institutions and mechanisms that allow cities to coordinate their positions and develop common approaches. These include the World Association of United Cities and Local Authorities, the World Assembly of Local and Regional Authorities, and the Metropolis Association. The main topics of today’s multilateral negotiations between cities include combating climate change, ensuring protection from natural disasters, promoting the rights of migrants and other displaced people, and fostering innovation in urban environment and governance. In contrast, bilateral negotiations between cities, based on the institution of sister cities, focus more on the humanitarian, scientific, educational, and cultural spheres of cooperation. Finally, current trends in international city negotiations include the increasing use of digital technologies and the geographical reorientation of Russian cities’ partnerships towards the countries of the “global majority.”